Immune Responses to Respiratory Syncytial Virus Vaccines: Advances and Challenges - Gabriela Souza da Silva; Sofia Giacomet Borges; Bruna Bastos Pozzebon; Ana Paula Duarte de Souza (Microorganisms, 2024)
Respiratory Syncytial Virus (RSV) is a leading cause of acute respiratory infections, particularly in children and the elderly. This virus primarily infects ciliated epithelial cells and activates alveolar macrophages and dendritic cells, triggering an innate antiviral response that releases pro-inflammatory cytokines. However, immunity generated by infection is limited, often leading to reinfection throughout life. This review focuses on the immune response elicited by newly developed and approved vaccines against RSV. A comprehensive search of clinical studies on RSV vaccine candidates conducted between 2013 and 2024 was performed. There are three primary target groups for RSV vaccines: pediatric populations, infants through maternal immunization, and the elderly. Different vaccine approaches address these groups, including subunit, live attenuated or chimeric, vector-based, and mRNA vaccines. To date, subunit RSV vaccines and the mRNA vaccine have been approved using the pre-fusion conformation of the F protein, which has been shown to induce strong immune responses. Nevertheless, several other vaccine candidates face challenges, such as modest increases in antibody production, highlighting the need for further research. Despite the success of the approved vaccines for adults older than 60 years and pregnant women, there remains a critical need for vaccines that can protect children older than six months, who are still highly vulnerable to RSV infections.